2015
DOI: 10.5194/amt-8-4329-2015
|View full text |Cite
|
Sign up to set email alerts
|

On the relative absorption strengths of water vapour in the blue wavelength range

Abstract: Abstract. In recent updates of the HITRAN water vapour H 2 O spectroscopic compilation covering the blue spectral region (here: 394-480 nm) significant changes for the absorption bands at 416 and 426 nm were reported. In order to investigate the consistency of the different cross-sections calculated from these compilations, H 2 O vapour column density ratios for different spectral intervals were retrieved from long-path and multi-axis differential optical absorption spectroscopy (DOAS) measurements. We observe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 67 publications
7
64
2
1
Order By: Relevance
“…Furthermore, the 430-480 nm retrieval window used by Wang et al (2014) contains both the 7ν (435-450 nm) and the 6ν +δ (460-480 nm) spectral bands of water vapor. Lampel et al (2015) derived scaling factors for the water vapor absorption bands in the blue spectral range using the 7ν band as a reference. They suggested that the absorption strength of the 6ν + δ band should be scaled by a factor of 1.02 ± 0.07 in HITRAN 2008 (Rothman et al, 2009).…”
Section: Omi and Ssmismentioning
confidence: 99%
“…Furthermore, the 430-480 nm retrieval window used by Wang et al (2014) contains both the 7ν (435-450 nm) and the 6ν +δ (460-480 nm) spectral bands of water vapor. Lampel et al (2015) derived scaling factors for the water vapor absorption bands in the blue spectral range using the 7ν band as a reference. They suggested that the absorption strength of the 6ν + δ band should be scaled by a factor of 1.02 ± 0.07 in HITRAN 2008 (Rothman et al, 2009).…”
Section: Omi and Ssmismentioning
confidence: 99%
“…We suggest addressing at the same time uncertainties in recent water vapour absorption cross sections (see e.g. Lampel et al, 2015b;Volkamer et al, 2015;Wilson et al, 2016 andLampel et al, 2017a) at around 419 and 360 nm in a controlled laboratory environment with wellknown light path lengths at different pressure and humidity values. The availability of such a data set has the potential to improve the spectral retrieval of various trace gases substantially as pointed out below.…”
Section: Discussionmentioning
confidence: 99%
“…From MAX-DOAS and LP-DOAS observations it was reported that these absorption lines are overestimated by a factor of 2 in HITRAN2012 (Lampel et al, 2015b), while the overall shape is relatively well reproduced. Thus the water vapour absorption contains some uncertainty, which could have an effect on the detection of the O 4 absorption band at 419 nm.…”
Section: Absorption Band At 419 Nmmentioning
confidence: 99%
See 2 more Smart Citations